Assessing the effectiveness of traction gels using full-scale and field testing. (July 2021) - White, Ben; Hyland-Knight, Jack; Lewis, Roger
Leaf fall during the autumn season creates low adhesion problems on the railways. Traction gels are used to prevent low adhesion, but very little testing has been carried out to assess their performance. Views on their effectiveness vary and their usage is inconsistent across the UK network as a result. This work developed a range of full-scale laboratory and field tests that can be used to assess traction gel performance. The outcomes can lead to increased industry confidence in their ability to mitigate low adhesion, as well as in future product development. It was shown that as a wheel passes over a puddle of traction gel on a rail head, that the gel element is squeezed away leaving the solid particles behind, pick-up on the wheel of particles was also evident. Traction gels were shown to increase traction in full-scale laboratory friction tests in dry and low adhesion conditions. Field brake tests showed that braking was effective in low adhesion and dry conditions with traction gel applied, matching the laboratory test results. The traction gel was also shown to remove a leaf layer, artificially produced by running a DMU over leaf material on a test track. Subsequent work should validate the results on a working railway line during the autumn season.